2018
DOI: 10.1111/ner.12742
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Electrical Stimulation for the Treatment of Chronic Ocular Pain and Photophobia

Abstract: Our data indicate that TENS may similarly provide analgesia in patients with dry eye symptoms as it does for many other chronic pain conditions. Furthermore, the noted effect on symptoms of photophobia and dryness suggest that all may be linked by similar trigeminal-thalamic-cortical pathways. Prospective studies with electrical stimulation of dry eye are needed to further elucidate its benefit and mechanism of action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…gabapentin), 2 , 4 and stimulation therapies. 17 , 18 In this case report, we describe the therapeutic potential of sensory peripheral nerve blocks and discuss possible mechanisms for their effect on eye pain.…”
Section: Introductionmentioning
confidence: 99%
“…gabapentin), 2 , 4 and stimulation therapies. 17 , 18 In this case report, we describe the therapeutic potential of sensory peripheral nerve blocks and discuss possible mechanisms for their effect on eye pain.…”
Section: Introductionmentioning
confidence: 99%
“…During medical procedures, it was not considered practical to only treat patients with TES without artificial tears as most patients were unwilling to receive TES treatment only without eye drops. Sivanesan et al (7) found that the non-invasive electrical stimulation of the trigeminal nerve achieved a short-term reduction in DE-related chronic ocular pain and photophobia. The use of TENS reduced pain intensity in both eyes by a mean of 57% and decreased light sensitivity by 27-28%.…”
Section: Discussionmentioning
confidence: 99%
“…The first hypothesis is that TES can effectively stimulate the trigeminal nerve to relieve DE symptoms such as pain and photophobia (7,29); this hypothesis may account for OSDI results. Previous studies reported that the mechanism of TES for DE may be associated with the modulation of neuroanatomical pain pathways within the trigeminal system (22,30,31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations